The Role of Elderly Cadres in Increasing Elderly Participation in Posyandu Activities in Margoyoso Village, Jayaloka District - Siti Rohana; Azizah Husin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to determine the role of elderly cadres in increasing the participation of the elderly in posyandu activities in Margoyoso Village, Jayaloka District. In this study using a type of qualitative descriptive research. With data collection methods using interviews, observation and documentation. The research subjects were posyandu cadres, elderly cadres, and the elderly. The research results obtained were: elderly cadres at posyandu activities in Margoyooso village in increasing the participation of elderly cadres in posyandu activities, namely there were four stages, namely the approach, communication, activity implementation, and service stages. The results obtained from the role of levels in these 4 aspects are quite good, but not optimal. The approach is only carried out at the start of the scheduled Posyandu. The communication carried out by elderly cadres is to convey information about the implementation of posyandu activities. Posyandu activities are carried out starting from elderly cadres preparing tools and places for carrying out activities, accompanying the elderly in having their health checked by health workers. Services performed by elderly cadres only provide promotive and preventive services and curative and rehabilitative services are provided by health workers or village midwives.